2021
DOI: 10.1177/07482337211022615
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive toxicity of cadmium in pubertal male rats induced by cell apoptosis

Abstract: Cadmium (Cd) is a heavy metal that is widely present in modern industrial production. It is a known, highly toxic environmental endocrine disruptor. Long-term exposure to Cd can cause varying degrees of damage to the liver, kidney, and reproductive system of organisms, especially the male reproductive system. This study aimed to explore the mechanism of Cd toxicity in the male reproductive system during puberty. Eighteen healthy 6-week-old male Sprague–Dawley rats were randomly divided into three groups (contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 70 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…Common environmental toxins include organic chemicals (such as herbicides, pesticides), metals and ionizing radiation. Numerous studies have found that Long-term exposure to environmental toxins can cause dysfunctions such as lung diseases ( 193 ), cancer ( 194 ), hepatic damage ( 195 ), especially the male reproductive disorders ( 196 ). For example, Bisphenol A (BPA) and formaldehyde are the widespread environmental pollutants, both of which can cause male reproductive injuries including testicular histopathological changes (decreased spermatogenic cells ( 144 ) or testicular tissue necrosis and edema ( 145 )), testicular oxidative stress damage(reducing testicular antioxidant enzyme activity ( 197 )) and cells apoptosis(up-regulating Bax apoptotic protein expression ( 145 )).…”
Section: The Protective Effects Of Taurine Against Male Reproductive ...mentioning
confidence: 99%
“…Common environmental toxins include organic chemicals (such as herbicides, pesticides), metals and ionizing radiation. Numerous studies have found that Long-term exposure to environmental toxins can cause dysfunctions such as lung diseases ( 193 ), cancer ( 194 ), hepatic damage ( 195 ), especially the male reproductive disorders ( 196 ). For example, Bisphenol A (BPA) and formaldehyde are the widespread environmental pollutants, both of which can cause male reproductive injuries including testicular histopathological changes (decreased spermatogenic cells ( 144 ) or testicular tissue necrosis and edema ( 145 )), testicular oxidative stress damage(reducing testicular antioxidant enzyme activity ( 197 )) and cells apoptosis(up-regulating Bax apoptotic protein expression ( 145 )).…”
Section: The Protective Effects Of Taurine Against Male Reproductive ...mentioning
confidence: 99%
“…It has been reported that plasma testosterone levels and testosterone synthase activity decreased after pubertal cadmium exposure, leading to defects in development of adolescent testes and reproductive dysfunction in adult mice [ 12 ]. Animal studies demonstrated that cadmium exposure resulted in testicular toxicity including abscission of epithelial cells, apoptosis of testicular germ cells and lower level of testosterone, eventually leading to spermatogenesis defects and declined sperm quality [ 13 , 14 ]. Nonetheless, the implications of cadmium-related damage to Leydig cells have received scant attention [ 15 , 16 ], and the underlying mechanism of cytotoxicity and apoptosis remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Cd-induced male reproductive toxicity has drawn the attention from many researchers [11,12].…”
Section: Introductionmentioning
confidence: 99%